Study on a Voltage Estimation of Tap‐Changing Transformer in Consideration of SVC Introduction. Issue 4 (June 2017) - YONEZAWA, SEIJI; MATSUOKA, NANAKO; TAKAYAMA, SATOSHI; ISHIGAME, ATSUSHI; MATSUURA, YASUO; ABE, KATSUYA; MINAMI, MASAHIRO
SUMMARY: Recent years, installation of photovoltaic (PV) system is active by the environmental problem and feed in tariff system. Due to PV's output fluctuation, the static var compensator (SVC) made by power electronics technology is planning to install in distribution system. The SVC is expected for maintain the voltage. But SVC differs in a theory of operation of the existing voltage controller load ratio control transformer (LRT) and step voltage regulator (SVR). Because the SVC operation makes the system impedance changes, the existing voltage controller may not operate effectively. In this study, the intelligent‐control method which used the radial basis function (RBF) network is proposed. This method can reduce the effects of the SVC operation by including the performance characteristics of SVC in the conventional method. An advantage of unnecessary arrangement attention of the SVC setup node and easy cooperation with the existing equipment is obtained by applying this method.